Diseño de un plan de mantenimiento preventivo para un sistema de recirculación de gases de escape en motores Isuzu de la serie N (2021)
This project focuses on presenting strategies based on preventive maintenance and correction of mechanical failures. This scientific article has with the purpose of carrying out a methodology of maintenance based on correction and prevention to an exhaust gas recirculation system of an Isuzu 4hk1-tc Diesel engine.The vehicle intervened was a special service bus from series F, in which the owner reported check engine light on and loss of power The bus.